High specific capacity oxygen / sulfur co-doped pitch-derived carbon microsphere negative electrode material and preparation method and application thereof
Patent Information
- Application Number
- CN202410310448.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-19
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-03-19
AI Technical Summary
因此,本发明提供一种高比容量氧/硫共掺杂沥青衍生碳微球负极材料及其制备方法和应用,可以有效解决沥青衍生碳微球缓慢的动力学导致的电化学性能差的问题
(1)所制备的氧/硫掺杂沥青衍生碳微球负极材料呈现均匀的球状结构,多数直径都在20μm左右,球状结构具有的优点是较高的体积能量密度、振实密度、热稳定性、化学稳定性及电热传导性。
Smart Images

Figure CN118183694B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery energy storage technology, specifically to a high specific capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material, its preparation method, and its application. Background Technology
[0002] With the widespread adoption of electric vehicles, lithium-ion batteries (LIBs), as a novel energy storage device, are widely used due to their long cycle life and high energy density. However, the scarcity and uneven distribution of lithium resources in the Earth's crust cannot meet the ever-increasing demand for energy storage. In contrast, the abundance and widespread distribution of sodium make sodium-ion batteries (SIBs) a candidate for renewable energy storage. However, because the ionic radius of sodium ions (1.02 Å) is much larger than that of lithium ions (0.76 Å), graphite, which is commercially used in lithium-ion batteries, exhibits extremely low specific capacity in sodium batteries. Therefore, the development of high-performance carbon anode materials plays a crucial role in the commercialization of SIBs.
[0003] Studies have shown that amorphous carbon anode materials are highly favored by researchers due to their unique disordered structure, and they are mainly divided into hard carbon and soft carbon. Hard carbon has a large interlayer spacing, abundant defect structure, and high specific surface area, and usually exhibits high reversible capacity, often being favored as a high-energy-density SIB. However, due to the excessive distortion of the graphite structure in hard carbon, poor conductivity is resulting in problems such as poor rate performance, high polarization, and low capacity. In contrast, soft carbon has good conductivity, exhibits excellent rate performance, and is well compatible with electrolytes, demonstrating excellent electrochemical stability. It also possesses an easily tunable microcrystalline structure, making soft carbon a promising candidate for sodium-ion battery anode materials.
[0004] As an excellent precursor to soft carbon, pitch is widely used due to its high carbon content, low price, and abundant sources. Structural design and morphology control of pitch-based carbon materials can unexpectedly improve the storage performance of sodium ions. Spherical soft carbon materials, in particular, are extensively studied due to their high volumetric energy density, tap density, thermal stability, chemical stability, and electrothermal conductivity. However, current pitch-derived carbon microsphere anode materials not only have complex preparation processes but also mostly exhibit poor kinetic performance, resulting in extremely low electrochemical performance.
[0005] Patent CN 116553511 A describes a process where asphalt raw materials and carbonaceous fillers are ground, sieved, and dried to obtain a solid mixture. This mixture is then melted and mixed with a viscosity reducer through heating and stirring to obtain a molten mixture. An aqueous solution containing a surfactant is pre-filled into a high-pressure reactor. The molten mixture is then slowly injected into the reactor from the bottom through a porous sieve plate for heating and stirring to obtain asphalt microspheres. The asphalt microspheres are then dried under reduced pressure and cured and cross-linked by heating in an air atmosphere. Subsequently, they are carbonized by heating in a nitrogen atmosphere to obtain asphalt-based hard carbon microsphere sodium storage material. This method uses water as a dispersion system and requires high-temperature and high-pressure reactions, which places high demands on equipment and has harsh process conditions. The resulting asphalt-based microspheres have limited capacity improvement in sodium-ion batteries.
[0006] Therefore, it is of great significance to design a high specific capacity pitch-derived carbon microsphere anode material through a simple method. Summary of the Invention
[0007] Current pitch-derived carbon microsphere anode materials suffer from complex preparation processes and often exhibit poor kinetic performance, resulting in extremely low electrochemical performance. Therefore, this invention provides a high-specific-capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material, its preparation method, and its applications. This effectively solves the problem of poor electrochemical performance caused by the slow kinetics of pitch-derived carbon microspheres. Furthermore, its simplified preparation process greatly facilitates large-scale production.
[0008] To achieve the above objectives, the technical solution of the present invention is implemented as follows: A method for preparing a high-specific-capacity oxygen / sulfur co-doped porous carbon anode material, comprising the following steps: (1) Disperse the anionic surfactant in silicone oil at a mass ratio of 1:150-200 to obtain a homogeneous mixture; crush the asphalt and sieve it through a 600-800 mesh screen to obtain asphalt powder; (2) Add the asphalt powder from step (1) to the mixing system at a mass ratio of 1:100-200, and stir and heat to obtain a uniform emulsion. The heating temperature is 260-290 ℃, and the reaction is carried out for 3-6 h. Before the end of heating, 2-3 h, a mixed gas containing oxygen is introduced into the bottom of the emulsion for bubbling oxidation. In the emulsion system, when the temperature exceeds the softening point of the asphalt powder, the asphalt powder becomes a flowing liquid. Due to its own surface tension and shear force, the asphalt liquid will continuously grow into spheres in the emulsion. Under the mixed gas containing oxygen, the spheres will not easily agglomerate. After the reaction is completed, wait for the emulsion to cool to room temperature, filter and wash, and finally vacuum dry the obtained solid to obtain a black powder. (3) Take the black powder and sulfur additive from step (2) and mix them evenly according to the mass ratio of 1:3-5; then carbonize them in a nitrogen atmosphere at 600-800℃ for 2-4 h to obtain high specific capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material.
[0009] Preferably, the asphalt in step (1) is any one or more of medium-low temperature coal tar pitch, refined asphalt, high temperature coal tar pitch, petroleum asphalt, and coal liquefaction asphalt; the sulfur additive in step (3) is any one or a combination of sublimed sulfur, thiourea, and ammonium sulfate.
[0010] Preferably, the silicone oil in step (1) is a high-temperature resistant silicone oil (resistant to 300°C); the anionic surfactant is one or more of sodium dodecylbenzenesulfonate, tetrapropylene benzenesulfonate ammonium, linear alkylbenzenesulfonate ammonium, and sodium oleoyloxyethanesulfonate.
[0011] Preferably, the oxygen-containing mixed gas in step (2) is a gas in which oxygen and nitrogen are mixed in a volume ratio of 1:1-5.
[0012] Preferably, the stirring speed in step (2) is 50-300 r / min.
[0013] Preferably, in step (2), the washing process is carried out sequentially with petroleum ether and acetone to remove the light components in the silicone oil and asphalt; the vacuum drying conditions are 50-80℃ for 6-10h.
[0014] Preferably, in step (3), the black powder and sulfur-adding agent are mixed by grinding or ball milling, wherein the ball milling time is 2-4 h and the rotation speed is 100-400 rmp.
[0015] The high specific capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material prepared according to the above method has a uniform spherical structure with a diameter of 5-20 μm.
[0016] Preferably, the oxygen and sulfur heteroatom content in the material is 16.1 at.%-30.5 at.%, wherein the oxygen to sulfur doping ratio is 2-4:1.
[0017] Preferably, the high specific capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material is used in sodium-ion batteries or lithium-ion batteries.
[0018] The present invention has the following beneficial effects: (1) The oxygen / sulfur doped pitch-derived carbon microsphere anode material prepared exhibits a uniform spherical structure, with most of them having a diameter of about 20 μm. The advantages of the spherical structure are high volumetric energy density, tap density, thermal stability, chemical stability and electrothermal conductivity.
[0019] (2) This invention achieves oxygen-doped asphalt by introducing oxygen into the asphalt emulsion. After ball milling and high-temperature calcination with a sulfur-enhancing agent, oxygen-sulfur atom co-doped carbon microspheres are obtained. The prepared asphalt-derived carbon microspheres have an oxygen-sulfur heteroatom content as high as 16.1 at.%-30.5 at.%. The oxygen / sulfur co-doped asphalt-derived carbon microsphere anode material has extremely rich surface oxygen-containing functional groups and sulfur-based functional groups, which greatly improves the sodium storage capacity of the asphalt-derived carbon microspheres. It has excellent electrochemical characteristics as a sodium-ion battery anode material. At a current density of 0.1 A / g, the reversible discharge specific capacity is 202-347.38 mAh / g.
[0020] (3) Conventional processes for preparing pitch-derived carbon microspheres are cumbersome and have low sodium storage performance, which is not conducive to large-scale production and application. The oxygen / sulfur co-doped pitch-derived carbon microspheres prepared in this invention can easily achieve a spherical structure with the assistance of oxygen cross-linking through secondary molecular cross-linking, and improve sodium storage performance under the action of sulfur cross-linking, which is conducive to large-scale industrial production and application. Attached Figure Description
[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0022] Figure 1 This is a SEM image of the oxygen / sulfur co-doped pitch-derived carbon microsphere anode material of Embodiment 1 of the present invention.
[0023] Figure 2 The image shows the XPS plot of the pitch-derived carbon microsphere anode material, where SOM-600 is the oxygen / sulfur co-doped pitch-derived carbon microsphere anode material of Example 1, and OM is the undoped pitch-derived carbon microsphere anode material of Comparative Example 1.
[0024] Figure 3 The graph shows the cycling performance of the pitch-derived carbon microsphere anode material; SOM-600 is the oxygen / sulfur co-doped pitch-derived carbon microsphere anode material of Example 1, and OM is the undoped pitch-derived carbon microsphere anode material of Comparative Example 1. Detailed Implementation
[0025] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0026] Example 1 A high-specific-capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material is prepared by the following steps: Sodium dodecylbenzenesulfonate and high-temperature resistant silicone oil in a mass ratio of 1:150 were added to a reaction vessel and stirred until a uniform mixture was obtained. Then, the refined asphalt was crushed in a multi-functional pulverizer and sieved using a 600-mesh stainless steel screen to obtain asphalt powder with a particle size of approximately 20 μm.
[0027] The 150g mixture obtained from the above process was added to a reaction vessel at a mass ratio of 100:1, along with 1.5g of sieved refined asphalt powder, and stirred and heated to obtain an emulsion system. The stirring speed was 100 r / min, and the temperature was maintained at 280℃ for 4 h. During the last two hours of heating, mixed air (oxygen:nitrogen volume ratio of 1:3) was bubbled into the bottom of the emulsion for oxidation at a flow rate of 100 mL / min. After heating, the emulsion was allowed to cool to room temperature, and the light components in the silicone oil and asphalt were washed away sequentially with petroleum ether and acetone. Finally, the resulting black powder was placed in an 80℃ oven and vacuum-dried for 8 h.
[0028] 0.1 g of the black powder and 0.3 g of sublimed sulfur prepared in the above steps were placed in a ball mill jar at a mass ratio of 1:3 and ball-milled for 2 h to ensure uniform mixing at a speed of 300 rpm. Then, the mixture was carbonized at 600 °C under a nitrogen atmosphere with a nitrogen flow rate of 200 mL / min to obtain a high-capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material for sodium-ion batteries. The SEM image of the obtained material is shown below. Figure 1 As shown, the high specific capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material exhibits a uniform spherical structure, with most having a diameter of around 20 μm and good sphericity.
[0029] XPS images of oxygen / sulfur co-doped pitch-derived carbon microsphere anode materials are shown below. Figure 2 As shown in the SOM-600 curve, the peaks of S 2p and S 2S are quite obvious, indicating that the S element was successfully doped after ball milling and carbonization. The oxygen and sulfur atom doping amount is 30.50 at.%, and the oxygen and sulfur atom doping ratio is 2:1.
[0030] The process of assembling a sodium-ion half-cell using it as the negative electrode material is as follows: Appropriate amounts of negative electrode material, polyvinylidene fluoride, acetylene black, and N-methylpyrrolidone were weighed at a mass ratio of 7:2:1. After ball milling at 200 rpm for 2 h, copper foil was uniformly coated onto the mixture, and the battery electrode was obtained after vacuum drying at 80℃ for 24 h. Using the obtained battery electrode as the working electrode and a sodium sheet as the counter electrode, sodium-ion button cells were assembled in a glove box. After assembly, the cells were allowed to stand for 12 h before their electrochemical performance was measured.
[0031] And test its electrochemical performance, such as Figure 3 As shown in the SOM-600 curve, the initial discharge specific capacity is 790.1 mAh / g at a current density of 0.1 A / g, and the discharge specific capacity can still reach 375.34 mAh / g after 100 cycles.
[0032] Example 2 A high-specific-capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material is prepared by the following steps: 1g of tetrapropylene benzenesulfonic acid ammonium and 150g of high-temperature resistant silicone oil in a mass ratio of 1:150 were added to a reaction vessel and stirred evenly to obtain a homogeneous mixture. Then, the high-temperature coal tar pitch was crushed in a multi-functional pulverizer and sieved using a 700-mesh stainless steel screen to obtain asphalt powder with a particle size of approximately 20μm.
[0033] Take 150g of the mixture obtained in the above process; add it to a reaction vessel along with 1.0g of sieved high-temperature coal tar pitch powder at a mass ratio of 150:1 and stir and heat to obtain a homogeneous emulsion system. The stirring speed is 100 r / min, and the temperature is maintained at 260℃ for 6 h. During the last two hours of heating, mixed air (oxygen:nitrogen volume ratio of 1:5) is bubbled into the bottom of the emulsion for oxidation at a flow rate of 100 mL / min. After heating, wait for the emulsion to cool to room temperature and then wash away the light components in the silicone oil and pitch with petroleum ether and acetone respectively. Finally, place the resulting black powder in a 50℃ oven and vacuum dry for 10 h.
[0034] 0.1 g of black powder and 0.5 g of thiourea prepared in the above steps were placed in a ball mill jar at a mass ratio of 1:5 and ball milled for 2 h to mix them evenly at a speed of 400 rpm. Then, the mixture was carbonized at 600 °C under a nitrogen atmosphere for 4 h, with a nitrogen flow rate of 200 mL / min, to obtain a high specific capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material. The oxygen and sulfur atom doping amount in this material was 16.10 at.%, and the oxygen-sulfur atom doping ratio was 2:1.
[0035] The oxygen / sulfur co-doped pitch-derived carbon microsphere anode material obtained in this embodiment is used as the electrode anode material to assemble a sodium-ion half-cell. The steps are as follows: Appropriate amounts of negative electrode material, polyvinylidene fluoride, acetylene black, and N-methylpyrrolidone were weighed at a mass ratio of 7:2:1. After ball milling at 200 rpm for 2 h, copper foil was uniformly coated onto the mixture, and the battery electrode was obtained after vacuum drying at 80℃ for 24 h. Using the obtained battery electrode as the working electrode and a sodium sheet as the counter electrode, sodium-ion button cells were assembled in a glove box. After assembly, the cells were allowed to stand for 12 h before their electrochemical performance was measured.
[0036] Its electrochemical performance was tested, and the initial discharge specific capacity was 400.1 mAh / g at a current density of 0.1 A / g, and the discharge specific capacity still reached 202.64 mAh / g after 100 cycles.
[0037] Example 3 A high-specific-capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material is prepared by the following steps: 1g of linear alkylbenzene sulfonic acid ammonium and 180g of high-temperature resistant silicone oil in a mass ratio of 1:180 were added to a reaction vessel and stirred until a homogeneous mixture was obtained. Then, the petroleum asphalt was crushed in a multi-functional pulverizer and sieved using an 800-mesh stainless steel screen to obtain petroleum asphalt powder with a particle size of approximately 20μm.
[0038] 200g of the homogeneous mixture obtained from the above process was added to a reaction vessel along with 1.0g of sieved petroleum asphalt powder at a mass ratio of 200:1 and stirred and heated to obtain a homogeneous emulsion system. The stirring speed was 100 r / min, and the temperature was maintained at 290℃ for 3 h. During the last two hours of heating, mixed air (oxygen:nitrogen volume ratio of 1:1) was bubbled into the bottom of the emulsion for oxidation at a flow rate of 100 mL / min. After heating, the emulsion was allowed to cool to room temperature and then washed with petroleum ether and acetone to remove the light components from the silicone oil and asphalt. Finally, the resulting black powder was placed in an 80℃ oven and vacuum-dried for 6 h.
[0039] 0.1 g of the black powder and 0.3 g of sublimed sulfur prepared in the above steps were placed in a ball mill jar at a mass ratio of 1:3 and ball milled for 4 h to mix them evenly at a speed of 300 rpm. Then, the mixture was carbonized at 700 °C under a nitrogen atmosphere with a nitrogen flow rate of 200 mL / min to obtain a high specific capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material. The oxygen and sulfur atom doping amount in this material was 25.11 at.%, and the oxygen-sulfur atom doping ratio was 3:1.
[0040] The oxygen / sulfur co-doped pitch-derived carbon microsphere anode material obtained in this embodiment is used as the electrode anode material to assemble a sodium-ion half-cell. The steps are as follows: Appropriate amounts of negative electrode material, polyvinylidene fluoride, acetylene black, and N-methylpyrrolidone were weighed at a mass ratio of 7:2:1. After ball milling at 200 rpm for 2 h, copper foil was uniformly coated onto the mixture, and the battery electrode was obtained after vacuum drying at 80℃ for 24 h. Using the obtained battery electrode as the working electrode and a sodium sheet as the counter electrode, sodium-ion button cells were assembled in a glove box. After assembly, the cells were allowed to stand for 12 h before their electrochemical performance was measured.
[0041] Its electrochemical performance was tested, and the initial discharge specific capacity was 520.1 mAh / g at a current density of 0.1 A / g, and the discharge specific capacity still reached 301.34 mAh / g after 100 cycles.
[0042] Example 4 A high-specific-capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material is prepared by the following steps: 1g of sodium oleoyloxyethanesulfonate and 200g of high-temperature resistant silicone oil in a mass ratio of 1:200 were added to a reaction vessel and stirred until a uniform mixture was obtained. Then, the coal liquefaction pitch was crushed in a multi-functional pulverizer and sieved using a 600-mesh stainless steel screen to obtain pitch powder with a particle size of 5~20μm.
[0043] 150g of the mixture obtained in the above process was added to a reaction vessel at a mass ratio of 100:1 and mixed with 1.5g of sieved coal liquefaction pitch powder. The mixture was stirred and heated to obtain an emulsion system. The stirring speed was 100 r / min, and the temperature was maintained at 280℃ for 4 h. During the last two hours of heating, mixed air (oxygen:nitrogen volume ratio of 1:2) was bubbled into the bottom of the emulsion for oxidation. The air flow rate was 100 mL / min. After heating, the emulsion was allowed to cool to room temperature and the light components in the silicone oil and pitch were washed away sequentially with petroleum ether and acetone. Finally, the resulting black powder was placed in an oven at 80℃ and dried under vacuum for 8 h.
[0044] 0.1 g of black powder and 0.5 g of sublimed sulfur prepared in the above steps were ground evenly in a mass ratio of 1:5, and then carbonized at 800 °C for 2 h in a nitrogen atmosphere with a nitrogen flow rate of 200 mL / min to obtain a high specific capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material. The oxygen and sulfur atom doping amount in this material was 28.11 at.%, and the oxygen and sulfur atom doping ratio was 3:1.
[0045] The oxygen / sulfur co-doped pitch-derived carbon microsphere anode material obtained in this embodiment is used as the electrode anode material to assemble a sodium-ion half-cell. The steps are as follows: Appropriate amounts of negative electrode material, polyvinylidene fluoride, acetylene black, and N-methylpyrrolidone were weighed at a mass ratio of 7:2:1. After ball milling at 200 rpm for 2 h, copper foil was uniformly coated onto the mixture, and the battery electrode was obtained after vacuum drying at 80℃ for 24 h. Using the obtained battery electrode as the working electrode and a sodium sheet as the counter electrode, sodium-ion button cells were assembled in a glove box. After assembly, the cells were allowed to stand for 12 h before their electrochemical performance was measured.
[0046] Its electrochemical performance was tested, and the initial discharge specific capacity was 710.7 mAh / g at a current density of 0.1 A / g, and the discharge specific capacity was still 344.83 mAh / g after 100 cycles.
[0047] Example 5 A high-specific-capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material is prepared by the following steps: 1g of surfactant (sodium dodecylbenzenesulfonate and sodium oleoyloxyethanesulfonate in a 1:150 mass ratio) and 150g of high-temperature resistant silicone oil were added to a reaction vessel and stirred until homogeneous, thus obtaining a uniform mixture. The high-temperature coal tar pitch was then crushed in a multi-functional pulverizer and sieved using a 600-mesh stainless steel screen to obtain high-temperature coal tar pitch powder with a particle size of approximately 20μm.
[0048] 150g of the mixture obtained in the above process was added to a reaction vessel at a mass ratio of 150:1 and mixed with 1.0g of sieved high-temperature coal tar pitch powder. The mixture was stirred and heated to obtain an emulsion system. The stirring speed was 100 r / min, and the temperature was maintained at 280℃ for 4 h. During the last two hours of heating, mixed air (oxygen:nitrogen volume ratio of 1:2) was bubbled into the bottom of the emulsion for oxidation. The air flow rate was 100 mL / min. After heating, the emulsion was allowed to cool to room temperature and the light components in the silicone oil and pitch were washed away sequentially with petroleum ether and acetone. Finally, the resulting black powder was placed in an oven at 80℃ and dried under vacuum for 8 h.
[0049] 0.1 g of the black powder and 0.5 g of thiourea prepared in the above steps were placed in a ball mill jar at a mass ratio of 1:5 and ball milled for 4 h to mix them evenly at a speed of 100 rpm. Then, the mixture was carbonized at 700 °C under a nitrogen atmosphere with a nitrogen flow rate of 150 mL / min to obtain a high specific capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material. The oxygen and sulfur atom doping amount in this material was 20.71 at.%, and the oxygen and sulfur atom doping ratio was 2:1.
[0050] The oxygen / sulfur co-doped pitch-derived carbon microsphere anode material obtained in this embodiment is used as the electrode anode material to assemble a sodium-ion half-cell. The steps are as follows: Appropriate amounts of negative electrode material, polyvinylidene fluoride, acetylene black, and N-methylpyrrolidone were weighed at a mass ratio of 7:2:1. After ball milling at 200 rpm for 2 h, copper foil was uniformly coated onto the mixture, and the battery electrode was obtained after vacuum drying at 80℃ for 24 h. Using the obtained battery electrode as the working electrode and a sodium sheet as the counter electrode, sodium-ion button cells were assembled in a glove box. After assembly, the cells were allowed to stand for 12 h before their electrochemical performance was measured.
[0051] Its electrochemical performance was tested, and the initial discharge specific capacity was 625.4 mAh / g at a current density of 0.1 A / g, and the discharge specific capacity could still reach 284.6 mAh / g after 100 cycles.
[0052] Example 6 A high-specific-capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material is prepared by the following steps: 1g of linear alkylbenzene sulfonic acid ammonium and 180g of high-temperature resistant silicone oil in a mass ratio of 1:180 were added to a reaction vessel and stirred evenly to obtain a uniform mixture system. Then, coal liquefaction pitch was crushed in a multi-functional pulverizer and sieved using an 800-mesh stainless steel screen to obtain coal liquefaction pitch powder with a particle size of 20μm.
[0053] 150g of the mixture obtained in the above process was added to a reaction vessel at a mass ratio of 100:1 and mixed with 1.5g of sieved coal liquefaction pitch powder. The mixture was stirred and heated to obtain an emulsion system. The stirring speed was 100 r / min, and the temperature was maintained at 280℃ for 4 h. During the last two hours of heating, mixed air (oxygen:nitrogen volume ratio of 1:2) was bubbled into the bottom of the emulsion for oxidation. The air flow rate was 100 mL / min. After heating, the emulsion was allowed to cool to room temperature and the light components in the silicone oil and pitch were washed away sequentially with petroleum ether and acetone. Finally, the resulting black powder was placed in an oven at 80℃ and dried under vacuum for 8 h.
[0054] 0.1 g of the black powder and 0.5 g of ammonium sulfate prepared in the above steps were placed in a ball mill jar at a mass ratio of 1:5 and ball milled for 2 h to mix them evenly at a speed of 100 rpm. Then, the mixture was carbonized at 800 °C under a nitrogen atmosphere with a nitrogen flow rate of 200 mL / min to obtain a high specific capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material. The oxygen and sulfur atom doping amount in this material was 25.41 at.%, and the oxygen-sulfur atom doping ratio was 3:1.
[0055] The oxygen / sulfur co-doped pitch-derived carbon microsphere anode material obtained in this embodiment is used as the electrode anode material to assemble a sodium-ion half-cell. The steps are as follows: Appropriate amounts of negative electrode material, polyvinylidene fluoride, acetylene black, and N-methylpyrrolidone were weighed at a mass ratio of 7:2:1. After ball milling at 200 rpm for 2 h, copper foil was uniformly coated onto the mixture, and the battery electrode was obtained after vacuum drying at 80℃ for 24 h. Using the obtained battery electrode as the working electrode and a sodium sheet as the counter electrode, sodium-ion button cells were assembled in a glove box. After assembly, the cells were allowed to stand for 12 h before their electrochemical performance was measured.
[0056] Its electrochemical performance was tested, and the initial discharge specific capacity was 610.2 mAh / g at a current density of 0.1 A / g, and the discharge specific capacity was still 311.4 mAh / g after 100 cycles.
[0057] Comparative Example 1: This comparative example provides an undoped sulfur pitch-derived carbon microsphere anode material, the preparation steps of which are as follows: 1 g of sodium dodecylbenzenesulfonate and 150 g of high-temperature resistant silicone oil in a mass ratio of 1:150 were added to a reaction vessel and stirred until a uniform mixture was obtained. Then, the refined asphalt was crushed in a multi-functional pulverizer and sieved using a 600-mesh stainless steel screen to obtain asphalt powder with a particle size of 20 μm.
[0058] 150g of the mixture obtained in the above process was added to a reaction vessel at a mass ratio of 100:1 and mixed with 1.5g of sieved refined asphalt powder. The mixture was stirred and heated to obtain an emulsion system. The stirring speed was 100 r / min, and the temperature was maintained at 280℃ for 4 h. During the last two hours of heating, mixed air (oxygen:nitrogen volume ratio of 1:3) was bubbled into the bottom of the emulsion for oxidation. The air flow rate was 100 mL / min. After heating, the emulsion was allowed to cool to room temperature and the light components in the silicone oil and asphalt were washed away sequentially with petroleum ether and acetone. Finally, the resulting black powder was placed in an 80℃ oven and vacuum dried for 8 h.
[0059] The black powder was then carbonized at 600℃ under a nitrogen atmosphere for 2 h, with a nitrogen flow rate of 200 mL / min, to prepare a sodium-ion battery pitch-derived carbon microsphere anode material. The XPS image of the obtained pitch-derived carbon microsphere anode material is shown below. Figure 2 As shown in the OM, since it was not S-doped, its S 2p and S 2s peaks are not obvious, and the oxygen doping amount is 14.94 at.
[0060] A sodium-ion half-cell was assembled using undoped sulfur pitch-derived carbon microspheres as the anode material. The preparation process is as follows: Appropriate amounts of negative electrode material, polyvinylidene fluoride, acetylene black, and N-methylpyrrolidone were weighed at a mass ratio of 7:2:1. After ball milling at 200 rpm for 2 h, copper foil was uniformly coated onto the mixture, and the battery electrode was obtained after vacuum drying at 80℃ for 24 h. Using the obtained battery electrode as the working electrode and a sodium sheet as the counter electrode, sodium-ion button cells were assembled in a glove box. After assembly, the cells were allowed to stand for 12 h before their electrochemical performance was measured.
[0061] Electrochemical performance such as Figure 3 As shown in the OM curve, the initial discharge specific capacity at a current density of 0.1 A / g is 277.11 mAh / g, and the discharge specific capacity after 100 cycles is 107.61 mAh / g.
[0062] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a high-specific-capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material, characterized in that, The steps are as follows: (1) Disperse the anionic surfactant in silicone oil at a mass ratio of 1:150-200 to obtain a homogeneous mixture; crush the asphalt and sieve it through a 600-800 mesh screen to obtain asphalt powder; (2) Add the asphalt powder from step (1) to the mixing system at a mass ratio of 1:100-200, and stir and heat to obtain a uniform emulsion. The heating temperature is 260-290 ℃, and the reaction is carried out for 3-6 h. Before the end of heating, 2-3 h, introduce an oxygen-containing mixed gas into the bottom of the emulsion for bubbling oxidation. The oxygen-containing mixed gas is a mixture of oxygen and nitrogen in a volume ratio of 1:1-3. After the reaction is completed, wait for the emulsion to cool to room temperature, filter and wash it, and finally vacuum dry the obtained solid to obtain a black powder. (3) Take the black powder and sulfur additive from step (2) in a mass ratio of 1:3-5 and mix them evenly. Then, carbonize them in a nitrogen atmosphere at 600-800℃ for 2-4 h to obtain high specific capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material.
2. The method for preparing the high specific capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material according to claim 1, characterized in that: The asphalt in step (1) is any one or more of medium-low temperature coal tar pitch, refined asphalt, high temperature coal tar pitch, petroleum asphalt, and coal liquefaction asphalt; the sulfur additive in step (3) is any one or a combination of sublimed sulfur, thiourea, and ammonium sulfate.
3. The method for preparing a high specific capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material according to claim 2, characterized in that: The silicone oil in step (1) is a high-temperature resistant silicone oil, and the anionic surfactant is one or more of sodium dodecylbenzenesulfonate, tetrapropylene benzenesulfonate ammonium, linear alkylbenzenesulfonate ammonium, and sodium oleoyloxyethanesulfonate.
4. The method for preparing a high specific capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material according to claim 1, characterized in that: The stirring speed in step (2) is 50-300 r / min.
5. The method for preparing a high specific capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material according to claim 4, characterized in that: In step (2), the washing is carried out sequentially with petroleum ether and acetone; the vacuum drying conditions are 50-80℃ for 6-10 hours.
6. The method for preparing a high specific capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material according to claim 4, characterized in that: In step (3), the black powder and sulfur-adding agent are mixed by grinding or ball milling, wherein the ball milling time is 2-4 h and the rotation speed is 100-400 rmp.
7. A high-specific-capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material prepared by the method according to any one of claims 1-6, characterized in that: The high-capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material has a uniform spherical structure with a diameter of 5-20 μm.
8. The application of the high specific capacity oxygen / sulfur co-doped pitch-derived carbon microsphere anode material as described in claim 7 in sodium-ion batteries or lithium-ion batteries.
Citation Information
Patent Citations
Preparation method of asphalt-based carbon microsphere and application of asphalt-based carbon microsphere as sodium ion battery electrode material
CN110451475A